2017
DOI: 10.1513/annalsats.201612-1008oc
|View full text |Cite
|
Sign up to set email alerts
|

Refining Low Physical Activity Measurement Improves Frailty Assessment in Advanced Lung Disease and Survivors of Critical Illness

Abstract: The DASI improves the construct and predictive validity of frailty assessment in adults with advanced lung disease or recent critical illness. This simple questionnaire should replace the more complex MLTA in assessing the frailty phenotype in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 41 publications
1
32
1
Order By: Relevance
“…The results79 showed that the DASI performed better and had a less pronounced floor effect than MLTA in this patient population and was more predictive of frailty outcome. The DASI queries activities more relevant to adults with advanced lung disease or to survivors of critical illness, and thus can minimize misclassification of frailty attributable to low activity and can better discriminate between different levels of activities relevant to the fields of pulmonary and critical care medicine 79. The FFP is based on the experience of suburban community-dwelling older adults who had fewer activity limitations than adults with advanced lung disease or older survivors of acute respiratory failure 79.…”
Section: Clinically Advanced and Critical Patientsmentioning
confidence: 80%
See 1 more Smart Citation
“…The results79 showed that the DASI performed better and had a less pronounced floor effect than MLTA in this patient population and was more predictive of frailty outcome. The DASI queries activities more relevant to adults with advanced lung disease or to survivors of critical illness, and thus can minimize misclassification of frailty attributable to low activity and can better discriminate between different levels of activities relevant to the fields of pulmonary and critical care medicine 79. The FFP is based on the experience of suburban community-dwelling older adults who had fewer activity limitations than adults with advanced lung disease or older survivors of acute respiratory failure 79.…”
Section: Clinically Advanced and Critical Patientsmentioning
confidence: 80%
“…In this study,79 they measured frailty physical activity using the Duke Activity Scale Index (DASI) and the MLTA in two cohorts of patients (advanced lung disease patients awaiting lung transplantation and survivors of acute respiratory failure). The results79 showed that the DASI performed better and had a less pronounced floor effect than MLTA in this patient population and was more predictive of frailty outcome. The DASI queries activities more relevant to adults with advanced lung disease or to survivors of critical illness, and thus can minimize misclassification of frailty attributable to low activity and can better discriminate between different levels of activities relevant to the fields of pulmonary and critical care medicine 79.…”
Section: Clinically Advanced and Critical Patientsmentioning
confidence: 99%
“…Another limitation is our definition of FFP frailty. During the study period, we found that using a new metric for operationalizing the “low activity” domain for the 5-domain based FFP frailty measure improved the validity of FFP frailty assessment in lung transplant candidates (23). Although we previously demonstrated both the FFP-DASI and FFP-MLTA measures to be valid in advanced lung disease (4) and combining the two enriches our sample size and reduces missing data, it is possible that the hybrid measure could contribute to misclassification of frailty by FFP and thereby influence the differential association between SPPB and FFP frailty and risk of mortality after lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize missing data and maximize our FFP sample size, we defined frailty by FFP using a “best-measure” approach. We have previously shown that replacing the operational measure of the FFP low activity domain (the Minnesota Leisure Time Activity Questionnaire [MLTA] (21)) with a measure validated in cardiopulmonary disease (the Duke Activity Status Index questionnaire [DASI] (22)), better quantified frailty-attributable low activity in lung transplant candidates by improving multiple tests of validity, including predicting waitlist delisting or death (23). Over the study period, early participants completed only the MLTA survey, others both the MLTA and DASI, and later subjects only the DASI.…”
Section: Methodsmentioning
confidence: 99%
“…The FFP is an aggregate score of five constructs: low physical activity, slowness, weakness, shrinking, and exhaustion . We used a modified version of the FFP that has better construct and predictive validity in lung transplant candidates than the original measure that was developed in a community‐dwelling older population . Each construct is assigned “1” if present or “0” if absent, standardized to sex, height, and weight.…”
Section: Methodsmentioning
confidence: 99%